Berpikir Level Tinggi dan TPACK Calon Guru Matematika pada Pembelajaran Matematika Abad ke-21 - Yanuarto, Wanda Nugroho; Jaelani, Anton (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
In the 21st century, learning requires high-level thinking processes and mastery of technology. The benefits of using technology accompanied by high-level thinking include 1) having many alternative solutions to problems, 2) be a good co-worker, and 3) being more independent in finding solutions. Also, learning mathematics is one of the main lessons in class and has the main characteristics of structured learning and has a systematic flow. The attributes of existing mathematics learning may support the technology learning process, which also has an orderly system and algorithm. This study employed a cross-sectional survey-it exploring high-level thinking and TPACK in mathematics learning. The subject was 182 pre-service mathematics teachers in Universitas Muhammadiyah Purwokerto, Indonesia. This study showed high-level thinking, and TPACK indicated that the item was sufficient to perform factor analysis. The analysis results found that the Kaiser Meyer-Oikin (KMO) value for items in the high-level thinking construct questionnaire with 12 items showed 0.657 (l> 0.50). Subsequently, in TPACK construct questionnaire with 32 items showed 0.783. The results stated that higher-order thinking is the essential capital in learning mathematics. Therefore, learning mathematics also demands the dynamism of technological developments to support the success of learning mathematics.